2002
DOI: 10.1007/bf03018137
|View full text |Cite
|
Sign up to set email alerts
|

Management of sleep apnea in adults

Abstract: PPER airway patency is essential for normal respiratory function. The maintenance of a patent airway is dependent on the pharyngeal and laryngeal structures. However, during speech, deglutition, regurgitation and eructation, the laryngeal and epiglottis do close momentarily. This is a protective mechanism that occurs during normal respiratory activities. The morphologic structure of the upper airway is important in the maintenance of the patent airway during sleep and wakefulness. The nasal passage has a bony … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…OSA patients are more likely to be difficult to intubate and emergency airway equipment should be readily available. 67 A recent retrospective study found 22% of OSA patients were difficult to intubate. 68 Several factors, including obesity, retrognathia and increased neck circumference contribute to the increased difficulty with intubation.…”
Section: Is Prolonged Cardiovascular Monitoring Indicated?mentioning
confidence: 99%
See 1 more Smart Citation
“…OSA patients are more likely to be difficult to intubate and emergency airway equipment should be readily available. 67 A recent retrospective study found 22% of OSA patients were difficult to intubate. 68 Several factors, including obesity, retrognathia and increased neck circumference contribute to the increased difficulty with intubation.…”
Section: Is Prolonged Cardiovascular Monitoring Indicated?mentioning
confidence: 99%
“…62,66,67 The type of surgery and need for postoperative narcotic analgesics are probably more important than the choice of anesthetic (grade D). Individual case-control study 4 Case-series Case-series Poor quality prognostic cohort study Poor quality cohort study Poor quality case-control study 5 Expert opinion without explicit critical Expert opinion without explicit critical appraisal, or appraisal, or based on physiology, bench based on physiology, bench research or research or "first principles" "first principles" CEBM = centre for evidence based medicine; RCT = randomized controlled trial; Case-control studies for prognosis should be considered poor quality prognostic cohorts or case series (Level 4 …”
Section: Does the Type Of Anesthetic Influence Postoperative Management?mentioning
confidence: 99%
“…In the patient with OSA, episodes of apnea occur five or more times per hour of sleep, with an associated decrease in oxygen saturation (SaO 2 ) of more than 4%. 1 The patient with OSA may also have periods of hypopnea, a decrease in tidal volume. With these two factors common to the syndrome of OSA, the apnea-hypopnea index (AHI) is used to facilitate a diagnosis.…”
mentioning
confidence: 99%
“…1 Apnea is the cessation of airflow. In the patient with OSA, episodes of apnea occur five or more times per hour of sleep, with an associated decrease in oxygen saturation (SaO 2 ) of more than 4%.…”
mentioning
confidence: 99%
“…
Obstructive sleep apnea hypopnea syndrome (OSAHS) is largely underdiagnosed in the general population, because as few as 20% of cases are symptomatic [1][2][3][4] and as many as 80% of all cases of OSAHS are unrecognized by primary care practitioners [1,[5][6][7]. OSAHS is estimated to affect 4% of men and 2% of women in Western countries, with a male to female ratio of 2 to 1 [8][9][10][11][12].
…”
mentioning
confidence: 99%